Testing The Validity of Risk Management in Islamic Finance: The Hadith Point of View - Abdul Qoyum (University of Darussalam Gontor, 2021)
Risk management in Islamic finance can be seen as an important aspect for business operation. The nature of Islamic finance which is quite different compared to conventional counterparts since the existance of shariah principle affect the risk management is more crucial in Islamic finance. Nevertheless, the practice of risk management in Islamic finance must be in line with shariah. Hence, this paper aims to analyze the validity of risk management from the Hadist point of view. By conducting qualitative research through detecting the quality of Hadist, the study revealed that Risk management practice is in line with shariah principle. It is based on the Hadits narrated by Ibnu Hibban that from the text, including in the matan and sanad can be classified as hadits ‘shohih”. In addition, the practice of Risk management is comply to the fulfilment of maqosid syariah.